Peningkatan Pengetahuan Penggunaan Obat untuk Siswa Sekolah Dasar - Aji Winanta; Mega Octavia; M. Fariez Kurniawan (Universitas Muhammadiyah Yogyakarta, 2020)
Public understanding of the use of drugs that are not true can cause new health problems. This empowerment activity aims to increase people’s understanding on medicine. This activity was conducted at SD Muhammadiyah Demangan Yogyakarta. The activities were conducted in stages, including joint program planning, tutorials (lectures), practice of recognizing and understanding medicine, mentoring, and recitation on understanding medicine. The main topic of discussion is knowledge about medicine, then added knowledge about healthy snacks, vitamins and their benefits for the body, as well as the role of the pharmacist profession in pharmaceutical services. The results of this service show an increase in the understanding of elementary school students about the use of drugs, healthy snacks, vitamins and their functions for the body as well as knowledge related to the pharmacist profession. There were 26 students of the 30 students who participated in the drug use assistance whose posttest scores improved compared to the pretest scores.